♥ To solve this you are going to find x. ♥
♥ X in this case is representing a unknown variable, meaning we are not sure of the number x, and to finish the solution to your problem we have to find x.
♥ So to find x the first step is to simplify both sides of the equation.
♥ Starting with distribution:
[tex]6=(-3)(x)+(-3)(2) \\ 6=-3x+-6 \\ 6=-3x-6[/tex]
♥ Now we want to flip the equation.
[tex]-3x-6=6[/tex]
♥ Our next and almost final step, is to add the number -3 to both sides of our problem. This is going to help us tremendously.
[tex]-3x-6+6=6+6 \\ -3x=12[/tex]
♥ Now our last step before we get our answer is to divide both sides of the problem. In this case we are going to do this:
[tex] \frac{-3x}{-3} = \frac{12}{-3} [/tex]
♥ And then because of that we get our final answer of: -4.
♥ x=-4 ♥